Uneven Learning Landscapes Ahead: Instructor Perspectives on Undergraduate Student Mental Health - Parizeau, Kate (Canadian Journal of Higher Education, 2022)
This study investigates instructor perspectives on undergraduate student mental health in a mid-sized comprehensive univer-sity in southwestern Ontario. Through a survey (n = 190) and two focus group discussions (n = 8), instructors reported differ-ent perspectives toward student mental health (some inclusive, some tolerant, and some discriminatory); changing workloads and pressures associated with addressing student mental health; and a predominant framing of mental health conditions as biomedical concerns. Using the conceptual framework of learning landscapes (Noyes, 2004), I argue that students with mental health concerns experience uneven and sometimes inequitable learning environments across their post-secondary education due to the differing microclimates created by individual instructors. While institutional policies and advocacy efforts to support mental health on campus may help to shift the learning landscape, they are unlikely to change the biases exhibited by some instructors that represent barriers to accessible post-secondary education.